Analisis faktor produksi terhadap kepuasan petani dalam mendorong ketahanan pangan di Sulawesi Selatan - Andi Arifuddin Iskandar (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The aim of this study is to determine whether farmers' satisfaction with the use of production factors contributes to the success of the Food Security System (SKP) and to identify which production factors most significantly influence farmers' satisfaction in supporting SKP. The research used a survey with Likert Scale data from 100 randomly selected rice farmers in Mattirobulu, Tiroang, Patampanua, and Duampanua districts, Pinrang Regency, South Sulawesi. The regression analysis showed a coefficient of determination of 100%, meaning that farmer satisfaction (dependent variable) is fully explained by the production factors (independent variable) and is not significantly influenced by external factors such as pests, diseases, natural disasters, or environmental conditions. The results indicated that the production process was operating at decreasing returns to scale (RTS), implying inefficiency in the use of production factors. Notably, the high overhead costs in pharmaceuticals (factor 4) need to be reduced by improving three key variables: farmer's land, information technology, and credit capital. This can be achieved by increasing land rent or profit-sharing, adopting advanced technology, and enhancing capital access through banking credit to improve farmer satisfaction and support SKP in Pinrang Regency.